Innovative therapeutic strategies targeting the network architecture of glioblastoma: clinical cancer research - Beichert, Julius; Hoffmann, Dirk C.; Winkler, Frank; Ratliff, Miriam (Clinical cancer research, 2025)
Recent discoveries concerning the network architecture of glioblastoma, including tumor microtubules and neuron-glioma synapses, have underscored critical pathways that sustain tumor growth, enhance resistance, and integrate glioblastoma with the surrounding neural environment. This review explores emerging therapeutic strategies targeting these pathways, including inhibitors of gap junctions, α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptors, and glutamate signaling, which are currently being tested in clinical trials. By consolidating these advances, this review seeks to bridge the gap between neurobiology, cancer neuroscience, and oncology, proposing novel approaches to overcome resistance and improve patient outcomes. The insights derived from this comprehensive review hold the potential to significantly influence the future management of glioblastoma.
Gesehen am 26.08.2025